Periodontal and Periapical Responses to Mandibular Incisor Intrusion: Conventional Method Vs. Bone Anchorage - Esen Aydoğdu; Ömür Polat-Özsoy; Mehmet Coşkun; Bahar Füsun Oduncuoğlu; Ayşe Gülsahi (Galenos Yayinevi, 2011)
Aim:To investigate the gingival and periapical side effects of mandibular incisor intrusion using mini-implants and to compare these with those of a conventional mandibular incisor intrusion mechanic, the utility arch.Subjects and Methods:26 deep bite patients were enrolled to one of the 2 groups. In the first group, mandibular incisors were intruded using 2 mini- implants and in the second group, using a conventional utility arch. The gingival reactions following intrusion were evaluated by pocket depth (PD), gingival index (GI), plaque index (PI), the width of keratinized gingiva (WKG) measurements at pretreatment (T0), pre-intrusion (T1) and at the end of intrusion (T2). Presence of root resorption was evaluated using both periapical radiographs and computed tomograms. Intragroup comparisons were made using a Paired t-test or Wilcoxon test. Intergroup comparisons were made using Student's t-test or Mann Whitney-U test.Results:In both groups, SD in the buccal side, GI, PI, WKG on buccal side and on lingual SD showed an increase at T2 compared to T0 and T1. PI on lingual side showed an increase from T0 to T2 in implant group but no differences were noted in utility arch group. Intergroup differences were found similar. Some amount of root shortening (0.08%% to 4.4%%) was measured on both periapical radiographs and tomograms.Conclusions:Similar changes in SD, GI, PI and WKG and root resorption were found with intrusion using the two methods. Root density measurements on CT images showed only minor density changes.